Key factors in the formation of social housing for internally displaced persons in Ukraine - Kutsalo, Oleksii (КНУБА, 2024)
The results of the analysis of key factors determining the directions of social housing formation for internally displaced persons (IDPs) in Ukraine are presented. Demographic, economic, psychological, and technological aspects influencing the development and implementation of housing projects for IDPs are examined. Based on the analysis, the main challenges and opportunities in the field of social housing creation under conditions of mass internal displacement are identified. Various approaches to housing policy formation are considered, taking into account diverse aspects of the problem and the needs of IDP integration.
Keywords: social housing; internally displaced persons; housing policy; demographic changes; psychological adaptation; innovative construction technologies; 728.2:351.84(477)